INTERVENSI BRAIN GYM LEBIH BAIK DALAM MENINGKATKAN KETERAMPILAN MOTORIK HALUS ANAK PRASEKOLAH (USIA 5-6 TAHUN) DARIPADA AKTIVITAS FUNGSIONAL DAN REKREASI (AFR) - Ni Putu Purnamawati; Ni Luh Nopi Andayani Andayani; I Made Muliarta (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2017)
ABSTRAK Lack of attention and stimulation from parents led to increased dependence of children to parents. Lack of stimulation from parents led to delays in the development of fine motor skills of children. Disability of children do fine motor movements are movements that involve small muscles like writing in accordance with his age can cause a child to feel insecure and inferior. This study is an experimental research using randomized designs Pre and Post Test Two Group Design dengab sampling technique is simple random sampling. The treatment group was given training Brain Gym I and II treatment groups are given functional and recreational activities (AFR). Results of paired samples t-test found a significant difference with p = 0.000 (p <0.05) in group I and group II. Different test difference with Mann Whitney showed a significant difference between the treatment groups I and II treatment group p = 0.000 (p <0.05), it was concluded that the intervention of the Brain Gym is better in improving the fine motor skills of preschool children (ages 5-6 years) rather than functional and recreational activities (AFR). Keywords: fine motor skills, stimulation, Brain Gym, AFR